Prisonization: Structure and Dynamics of the Phenomenon in State Jails of the Chilean Penal System - Romero Miranda, Luis Alejandro (FLACSO - Sede Ecuador, 2019)
This article presents the main results of the qualitative research entitled "Representations and Implications of prisonization in a Group of Former Convicts of the Chilean Criminal System", developed between November 2016 and April 2018, as part of the annual work plan of the Program of Investigation and Delictual Analysis of the Universidad La República. The sample is composed by 16 male ex-convicts from state prisons in the metropolitan region and Valparaíso. As main findings, the interviews show recurring milestones or experiences that allow us to propose a common sequence in the genesis and structuring of prisonization (phases). The latter is mediated by the life trajectory, the adherence to institutional / subcultural norms, the entry position in the subcultural hierarchy and the capacity of the subject to move or settle within it.